2019
DOI: 10.2147/ijn.s199695
|View full text |Cite
|
Sign up to set email alerts
|

<p>EGFP-EGF1-conjugated poly(lactic-co-glycolic acid) nanoparticles, a new diagnostic tool and drug carrier for atherosclerosis</p>

Abstract: Background: EGFP-EGF1-conjugated poly(lactic-co-glycolic acid) (PLGA) nanoparticle (ENP) has a specific affinity to tissue factor (TF). The aim of this study was to investigate the target delivery of ENP to plaques and its uptake in a mouse model of atherosclerosis in vivo and in vitro. Materials and methods: Coumarin-6-and 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindotricarbo cyanine iodide (DiR)-loaded ENPs were synthesized using a double-emulsion method. Mouse vascular smooth muscle cells (VSMCs) were induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It has been proved that ENP's can mediate target delivery of TF-siRNA to injured brain micro-vascular endothelial cells (BMECs) for effective TF gene silencing in rats 19 . We also found that ENPs exhibited specific binding to atherosclerotic cellular model of vessel smooth muscle cells and plaques in an animal model 20 . We hypothesize that ENPs could also effectively adhere to atherosclerotic macrophages via binding to TF protein on cell surface.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…It has been proved that ENP's can mediate target delivery of TF-siRNA to injured brain micro-vascular endothelial cells (BMECs) for effective TF gene silencing in rats 19 . We also found that ENPs exhibited specific binding to atherosclerotic cellular model of vessel smooth muscle cells and plaques in an animal model 20 . We hypothesize that ENPs could also effectively adhere to atherosclerotic macrophages via binding to TF protein on cell surface.…”
mentioning
confidence: 51%
“…CCR2-shRNA loaded PLGA nanoparticles, Coumarin-6 loaded EGFP-EGF1-PLGA nanoparticles and CCR2-shRNA loaded EGFP-EGF1-PLGA nanoparticles were prepared using a water in oil in water (w/o/w) double emulsion solvent evaporation method as previously described 22,23 . The characterization and loading efficiency of nanoparticles were determined as before 20 . Drug loading capacity (DLC) and drug encapsulation efficiency (DEE) were calculated according to the following equations:…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were sealed with 5% (w/v) bovine serum albumin (BSA) at room temperature for 30 min. 18 , 31 , 50 The Sealed membranes were incubated with appropriate primary and secondary antibodies. The super-signal west picochemiluminescent substrate kit (Pierce Biotechnology; MA, USA) was used for blot development.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were separated using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and transferred to nitrocellulose membranes. The membranes were sealed with 5% (w/v) bovine serum albumin (BSA) at room temperature for 30 min. ,, The Sealed membranes were incubated with appropriate primary and secondary antibodies. The super-signal west picochemiluminescent substrate kit (Pierce Biotechnology; MA, USA) was used for blot development.…”
Section: Methodsmentioning
confidence: 99%
“…There are generally no symptoms in the early stages of atherosclerosis and traditional detection techniques cannot easily, safely, and effectively detect the lesions in the early stages [8,9] . In recent years, there has been a rapid development in using nano-carrier technique as a tool for molecular imaging of atherosclerotic lesion [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%